TYPOLOGICAL CONTRASTS OF THE RUSSIAN AND UZBEK LANGUAGES IN THE METHODOLOGICAL ASPECT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Methodological directions for studying the grammatical structure of the Uzbek and Russian languages (including in a comparative aspect) in Uzbekistan have long traditions and are currently actively developing, a large number of textbooks on this topic are being published. However, a common drawback of most of such publications, from our point of view, is insufficient attention to the typological contrasts of the grammatical systems of the Uzbek and Russian languages, namely, they create “problem” areas for the assimilation of these languages.